2021
DOI: 10.1016/s2468-2667(21)00096-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different types of written vaccination information on COVID-19 vaccine hesitancy in the UK (OCEANS-III): a single-blind, parallel-group, randomised controlled trial

Abstract: Background The effectiveness of the COVID-19 vaccination programme depends on mass participation: the greater the number of people vaccinated, the less risk to the population. Concise, persuasive messaging is crucial, particularly given substantial levels of vaccine hesitancy in the UK. Our aim was to test which types of written information about COVID-19 vaccination, in addition to a statement of efficacy and safety, might increase vaccine acceptance. Methods For this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
242
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(264 citation statements)
references
References 10 publications
(7 reference statements)
17
242
3
2
Order By: Relevance
“…This was particularly true during the COVID-19 immunization campaign, as the fast pace of vaccine development-exceptional but unprecedentedcontributed to rise doubts upon vaccination safety and effectiveness [41,42]. However, some large surveys from the UK suggested that the chances of vaccination increased, even among the more reluctant subgroups, once it was acknowledged that the immunization significantly reduced the risk of severe disease [40,43]. Similarly, the probability of being vaccinated was substantially increased after clear information upon the safety profile of a vaccine was provided [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was particularly true during the COVID-19 immunization campaign, as the fast pace of vaccine development-exceptional but unprecedentedcontributed to rise doubts upon vaccination safety and effectiveness [41,42]. However, some large surveys from the UK suggested that the chances of vaccination increased, even among the more reluctant subgroups, once it was acknowledged that the immunization significantly reduced the risk of severe disease [40,43]. Similarly, the probability of being vaccinated was substantially increased after clear information upon the safety profile of a vaccine was provided [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, some large surveys from the UK suggested that the chances of vaccination increased, even among the more reluctant subgroups, once it was acknowledged that the immunization significantly reduced the risk of severe disease [40,43]. Similarly, the probability of being vaccinated was substantially increased after clear information upon the safety profile of a vaccine was provided [43]. In this scenario, our study, based upon real-world data, may have important practical implications for public health policy, as it may help reassure the general population on both the effectiveness and the safety of the most widely used COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…To untangle the complex interplay of vaccine benefits in shaping the U.S. public’s vaccination behavior, we focused on three aspects of vaccine benefits individual, community, and country benefits. First, the individual or personal benefits such as protecting personal health and gaining access to public facilities have long been identified as important motivators of vaccination [8] , [9] . Second, research indicates that people vaccinate themselves or their children not only for personal gains, but also to safeguard the wellbeing of their community [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Oxford Coronavirus Explanations, Attitudes, and Narratives Survey (OCEANS) III (Freeman et al, 2021 ) is an online survey with a quota sampled UK participant group of 15 014 adults (18+ years old), conducted from 19 January 2021 to the 5 February 2021 via a market research company, Lucid. The quotas were based on UK Office for National Statistics population estimate data for gender, age, ethnicity, income and region.…”
Section: Methodsmentioning
confidence: 99%
“…A fear of fainting may cause great reluctance to join a line of people waiting for a vaccine injection. In our latest UK survey (Freeman et al, 2021 ), we therefore included assessment of blood-injection-injury fears in order to determine the degree to which they may be a factor in hesitancy about COVID-19 vaccination, which currently depends on injection.…”
Section: Introductionmentioning
confidence: 99%